Involvement of women in the stunting convergence program policy in the coastal area of Ketapang Regency - Rupita Rupita; Arkanudin Arkanudin; Sudirman Sudirman; Yulianti Yulianti; Ignasia Debby Batuallo (Journal of Governance, 2022)
West Kalimantan is one of the provinces that has a high prevalence of stunting compared to other provinces in Indonesia. One of the biggest contributors to stunting prevalence is Ketapang district. Therefore, this study aims to find out further stunting mapping in Ketapang district and see how women's involvement in the convergence program is a strategy in dealing with stunting in the coastal areas of Ketapang Regency. This study uses a qualitative approach with descriptive analysis with data collection techniques through observation, in-depth interviews, and documentation studies. The results showed that stunting cases in Ketapang district showed a declining trend due to the success of the community empowerment program for all female cadres by conducting stunting prevention training through the process of extracting knowledge of female stunting cadres and increasing the capacity of female stunting cadres.